Theoretical and experimental study on the performance of a diesel engine fueled with diesel-biodiesel blends - Gonca, Guven; Dobrucali, Erinc (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This study reports the effects of engine load and biodiesel percentage on the performance of a diesel engine fueled with diesel biodiesel blends by experiments and a new theoretical model based on the finite-time thermodynamics (FIT). In recent years, biodiesel utilization in diesel engines has been popular due to depletion of petroleum-based diesel fuel. In this study, performance of a single cylinder, four-stroke, direct injection (DI) diesel engine fueled with diesel biodiesel mixtures has been experimentally and theoretically investigated. The simulation results agree with the experimental data. After model validation, the effects of engine load and biodiesel percentage on engine performance have been parametrically investigated. The results showed that, effective power increases constantly, effective efficiency increases to a specified value and then starts to decrease with increasing engine load at constant biodiesel percentage and compression ratio. However, effective efficiency increases, effective power decreases to a certain value and then begins to increase with increasing biodiesel percentage at constant equivalence ratio and compression ratio. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Biodiesel; Engine performance; Performance optimization; Finite-time thermodynamics; COMBUSTION CHARACTERISTICS; STEAM INJECTION; VEGETABLE-OILS; MILLER CYCLE; EMISSION CHARACTERISTICS; HEAT-TRANSFER; METHYL-ESTERS; STANDARD; SPECIFICATIONS; PARAMETERS; Science & Technology - Other Topics; Energy & Fuels